Effects of passion fruit peel flour (Passiflora edulis f. flavicarpa O. Deg.) in cafeteria diet-induced metabolic disorders. (25th March 2020) - De Faveri, Aline; De Faveri, Renata; Broering, Milena Fronza; Bousfield, Izabel Terranova; Goss, Marina Jagielski; Muller, Samuel Paulo; Pereira, Raquel Oliveira; de Oliveira e Silva, Ana Mara; Machado, Isabel Daufenback; Quintão, Nara Lins Meira; Santin, José Roberto
Abstract: Ethnopharmacological relevance: Passiflora edulis f. flavicarpa O. Deg. is a native Brazilian fruit known as sour or yellow passion fruit. From its peel, mainly in the northeast of Brazil, is produced a flour that is largely used as folk medicine to treat diabetes and other metabolic conditions. Aim of the study: The aim of the study was to show the effects of P. edulis peel flour (PEPF) in metabolic disorders caused by cafeteria diet in mice. Material and methods: The antioxidant activity in vitro of PEPF extract was determined by ferric reducing/antioxidant power, β-carotene/linoleic acid system and nitric oxide scavenging activity assay. C57BL/6 mice divided in 3 groups: Control group, fed on a standard diet (AIN); Cafeteria diet (CAF) group, fed on a cafeteria diet, and PEPF group, fed on a cafeteria diet containing 15% of PEPF, during 16 weeks. The glucose tolerance and insulin sensitivity were evaluated through the glucose tolerance test (GTT) and the insulin tolerance test (ITT). After the intervention period, blood, hepatic, pancreatic and adipose tissues were collected for biochemical and histological analysis. Cholesterol, triglyceride, interleukins and antioxidant enzymes were measured in the liver tissue. Results: PEPF extract presented antioxidant activity in the higher concentrations in the performed assays. The PEPF intake decreased the body weight gain, fat deposition, predominantly in the liver, improved the glucose tolerance and insulin sensitivity in metabolic changes caused by cafeteria diet. Conclusion: Together, the data herein obtained points out that P. edulis peel flour supplementation in metabolic syndrome condition induced by CAF-diet, prevents insulin and glucose resistance, hepatic steatosis and adiposity. Graphical abstract: Image 1